Experimental Evaluation of JANUS Fast Modes in Very High Acoustic Frequency Bands - Li, Jinfeng; Zheng, Yahong Rosa (IEEE journal of oceanic engineering, 2023)
This article presents extensive field tests of a fast-mode operation of the JANUS acoustic communication standard where the signals occupy high-frequency bands of 38 kHz spanning from 96 to 134 kHz instead of the nominal frequency band of 4.1 kHz spanning from 9.44 to 13.6 kHz specified in the standard. The fixed 32-chip preamble and the 144-chip baseline JANUS packet utilize the frequency-hopped binary frequency shift keying with 13 frequency pairs as defined in the standard while the cargo packets use the single-carrier M -ary phase shift keying modulation with a center frequency of 115 kHz and a symbol rate of 23 ksps or up to 34.5 kb/s information data rate with high-order phase shift keying (PSK) and rate-1/2 forward error correction codes. The original JANUS receiver algorithm is modified to improve the frame/symbol synchronization for the fast mode and increase the decoding success rate of the baseline JANUS packet in difficult multipath channels. More than 10 experiments were conducted using a field-programmable-gate-array-based hardware platform consisting of a single transmit projector and a single receive hydrophone. The experiment results show that the JANUS fast mode worked well with both the original JANUS receiver algorithm and the modified receiver algorithm, yielding zero bit error in most of the baseline JANUS packets. The modified receiver algorithm is able to reduce 30% of error packets to zero error in the experiment experiencing difficult multipath channels where the original JANUS receiver algorithm suffers from large bit error rates (BER). Meanwhile, the cargo packets utilize the linear minimum mean-square error turbo equalizer and achieve a BER around 10 −3 .